1996
DOI: 10.1093/jnci/88.23.1731
|View full text |Cite|
|
Sign up to set email alerts
|

KiSS-1, a Novel Human Malignant Melanoma Metastasis-Suppressor Gene

Abstract: KiSS-1 may be a useful marker for distinguishing metastatic melanomas from nonmetastatic melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
673
3
49

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 916 publications
(738 citation statements)
references
References 36 publications
(32 reference statements)
13
673
3
49
Order By: Relevance
“…The gene from which kisspeptins are transcribed, KISS1, is a tumor-suppressor gene in breast cancer cells, but later work has also identified products of this gene as an energy sensor (Lee et al, 1996). Earlier studies showed that GPR54 is expressed in hypothalamic neurons as well as in the pancreas and the placenta (Kotani et al, 2001).…”
Section: Gpr54mentioning
confidence: 99%
“…The gene from which kisspeptins are transcribed, KISS1, is a tumor-suppressor gene in breast cancer cells, but later work has also identified products of this gene as an energy sensor (Lee et al, 1996). Earlier studies showed that GPR54 is expressed in hypothalamic neurons as well as in the pancreas and the placenta (Kotani et al, 2001).…”
Section: Gpr54mentioning
confidence: 99%
“…1 To date, only a few such molecules are discovered and among them KiSS-1 is only recently discovered as a promising metastasis suppressor gene. 2 The KiSS-1 cDNA was originally cloned by subtraction hybridization between a metastatic and a nonmetastatic melanoma cell line and has been proved to be competent in ameliorating the metastatic potentiality of several cancer cell lines in in vitro study. 2,3 Significant reduction in KiSS-1 or metastin expression in tumors with high metastatic potential has been reported.…”
mentioning
confidence: 99%
“…2 The KiSS-1 cDNA was originally cloned by subtraction hybridization between a metastatic and a nonmetastatic melanoma cell line and has been proved to be competent in ameliorating the metastatic potentiality of several cancer cell lines in in vitro study. 2,3 Significant reduction in KiSS-1 or metastin expression in tumors with high metastatic potential has been reported. 4 -6 Moreover, reduced KiSS-1 expression became a strong prognostic marker in patients with urinary bladder cancer.…”
mentioning
confidence: 99%
“…1,2 Metastatic phenotypes have been linked to such genes as NME1 (17q), CDH1 (16q), BRMS1 (11q) and KISS1 (1q). 1,[3][4][5] LOH analyses have defined regions of deletion associated with metastasis on chromosomes 3p21, 15q14, 16q22 and 11p15. 2,6 Frequent genetic alterations on chromosome 11p15 suggest a crucial role for this region in breast 6,7 and other adult 8 -12 and childhood cancers.…”
mentioning
confidence: 99%